2019
DOI: 10.3168/jds.2018-14831
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Influence of an aqueous myrrh suspension on yogurt culture bacteria over yogurt shelf life

Abstract: Myrrh is an essential oil and natural flavoring approved by the US Food and Drug Administration, and it has antibacterial and antifungal activity against pathogens. Our objective was to determine the effect of an aqueous myrrh suspension on Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus counts in peptone solution and yogurt, as well as pH and titratable acidity of yogurt during 5 wk of storage at 1 to 4°C. The myrrh suspension (10% wt/vol) was prepared and incorporated into a pure cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…bulgaricus count compared to Y (P < 0.05). A similar observation was made by Alhejaili 46 in their attempt to find the influence of an aqueous myrrh (essential oil) suspension on yogurt culture bacteria.…”
Section: Changes In Phsupporting
confidence: 72%
See 1 more Smart Citation
“…bulgaricus count compared to Y (P < 0.05). A similar observation was made by Alhejaili 46 in their attempt to find the influence of an aqueous myrrh (essential oil) suspension on yogurt culture bacteria.…”
Section: Changes In Phsupporting
confidence: 72%
“…THe DPPH assay was performed to measure the antioxidant activity of different yogurt samples. As per the results (Figure b), LNEY exhibited a higher antioxidant activity of 30% on the first day that eventually increased to a maximum of 40% in the second week of storage due to the interaction of lycopene with biologically active peptides released from milk as a result of the metabolic and proteolytic activities in yogurt upon storage. Such a high level of radical scavenging activity in LNEY signifies the power of the nanoemulsion as an effective carrier for a sensitive antioxidant pigment like lycopene. In the case of LY, the maximum scavenging activity exhibited was during the first week (25%), and later, it was decreased to 20% during the fourth week of storage. The study of Erica and Vassilios indicated that the enhanced stability of the lycopene improved the antioxidant property of the lycopene-incorporated beverage emulsion.…”
Section: Resultsmentioning
confidence: 59%
“…Various levels of herb EOs can affect the activity of bifidobacteria and lactic acid bacteria (LAB) in dairy products and this has been evaluated by researchers (Mahmoudi, Zare, Hassanzadeh, & Nosratpour, ). The relationship between the concentration of DEO and antimicrobial effects remains uncertain, although some works have attributed the EO S antimicrobial characteristics to the presence of oxygenated monoterpenes in the EO, such as linalool, limonene, and α‐phellanoidrene (Alhejaili et al, ). Compared to other gram‐positive bacteria, LAB are usually considered as the most stable bacteria against essential oils of plants (Mahmoudi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Tseng and Zhao (2013) using of dietary fiber with thyme, garlic, and mint showed increase in probiotic bacteria population in yogurt during storage time. Various levels of herb EOs can affect the activity of bifidobacteria and lactic acid bacteria (LAB) in dairy products and this has been evaluated by researchers (Mahmoudi, Zare, Hassanzadeh, & Nosratpour, 2014 (Alhejaili et al, 2019). Compared to other gram-positive bacteria, LAB are usually considered as the most stable bacteria against essential oils of plants (Mahmoudi et al, 2014).…”
Section: Viability Of B Bifidum and L Caseimentioning
confidence: 99%
“…Titratable acidity was measured by titrating 10 g of the yogurt blended with 10 mL of distilled water using 0.1 N NaOH solution until pH 8.3. Titratable acidity was calculated as percent lactate (Alhejaili et al, 2019). Titratable acidity was calculated as below: Titratable acidity (%) = used NaOH (mL) × 0.009/weight of yogurt (g) × 100, where 0.009 is the conversion factor for lactic acid.…”
Section: Measurements Of Physicochemical Characteristicsmentioning
confidence: 99%